The Impact of Carbon Emission Disclosure, Green Investment, and Environmental Performance on Company value with Media Exposure as a Moderating Variable - Mubarok, M. Malik; Rosyadi, Imron (Universitas Muhammadiyah Surakarta, 2024)
The objective of this study is to examine the impact of carbon emission disclosure, green investment, and environmental performance on firm value, and to evaluate the role of media exposure as a moderating variable. The research method employed is quantitative, with data analysis conducted using Smart6 PLS. The sample comprises 175 data points from seven companies over the period 2019-2023. The findings of the study demonstrate that there is a statistically significant negative relationship between carbon emission disclosure and firm value. This implies that a high level of emission disclosure can lead to a reduction in the market value of a company. The results indicate that green investment does not have a significant effect on firm value. This suggests that the impact of green investment on firm value may be indirect or insignificant. In contrast, environmental performance demonstrates a significant positive effect on firm value, indicating that an increase in environmental performance is correlated with an increase in market value. Furthermore, the findings revealed that media exposure did not reinforce the favourable impact of environmental performance but, conversely, served to exacerbate the detrimental effect of carbon emission disclosure. The results of this study underscore the necessity of incorporating public and media perceptions into a company's sustainability strategy. Overall, this study offers comprehensive insights into the manner in which environmental sustainability factors influence firm value, both directly and through the role of the media.